Teachers' Mental Health: Protective Factors - Menghi, María Soledad (2018)
At present, the psychophysical health of educators is an issue that has taken on increased importance, especially the phenomenon of chronic work stress, as it directly affects the effectiveness of their work. Hence the importance of detecting what factors can prevent this chronic exhaustion in the educational field. This research aimed at answering this question from an empirical perspective. To this end, a sample of 300 early education and primary school teachers from both public and private institutions of the Argentina was used. Maslach and Jackson's Burnout Inventory (MBI) was implemented to determine the level of chronic stress. In order to assess two psychosocial resources of great relevance in the context of work, the Albert Bandura's Teaching Self-efficacy Scale and the Job Satisfaction Scale for educators were used. Overall, the perceptions of teacher self-efficacy and of job satisfaction are considered psychological resources that would act as modulators of chronic stress in the workplace, noticing moderate and high values in the resources, but low levels of burnout symptoms in the teacher sample evaluated.